Preliminary data on nematode infections in guinea pigs in the province of Cajabamba (Cajamarca, Peru). - Tacilla, K. (2024)
In the absence of local studies, the current study was conducted in four villages located in the province of Cajabamba (Cajamarca, Peru) to demonstrate and determine the point prevalence of enteric nematodes in guinea pigs (Cavia porcellus) raised in a family-commercial breeding system. A total of 384 faecal samples were collected from guinea pigs and processed using the Sheather Sugar method. The eggs of P. uncinata, Trichuris spp., and Capillaria spp. were identified in guinea pigs from all four villages, resulting in an overall prevalence of 66.15±4.73%. Among the villages, the highest prevalence was observed in Naranjos, with a prevalence of 78.16±8.68% (68 out of 87 guinea pigs). This was followed by Malcas with a prevalence of 67.24±8.54% (78 out of 116 guinea pigs), Ogosgуn-Paucamonte with a prevalence of 64.08±9.27% (66 out of 103 guinea pigs), and La Esperanza with a prevalence of 53.85±11.06% (42 out of 78 guinea pigs). Furthermore, it was found that 66.54±5.80% of guinea pigs had a single nematode, 28.35±5.54% had two nematodes, and 5.12±2.71% had three nematodes. Thus, the presence of enteric nematodes in guinea pigs raised in a family-commercial breeding system from four villages in the Cajabamba district was established.